Bone mineral density in young adults: the influence of vitamin D status, biochemical indicators, physical activity and body composition - Kopiczko, Anna (Arch Osteoporos, 2020)
SUMMARY: The aim of the study was to assess the associations of bone mineral density and bone mass with physical activity levels, vitamin D, phosphorus, magnesium, total cholesterol and triglyceride concentration and body composition in young women and men. Physical activity has the most significant effect on bone status especially in men. PURPOSE: The aim of the study was to assess the associations of bone mineral density and bone mass with physical activity levels, vitamin D, phosphorus, magnesium, total cholesterol and triglyceride concentration and body composition in young women and men. METHODS: One hundred subjects aged 19–24 years were included. Bone mineral density (BMD) in distal and proximal parts was evaluated by forearm densitometry. Body composition was analysed with the use of JAWON-Medical-x-scan. The following biochemical indicators were analysed: 25(OH) D and 1,25(OH)2D, magnesium, phosphorus, total cholesterol and triglycerides. Physical activity levels were assessed by interview. RESULTS: Significant correlations between BMD and physical activity, skeletal muscle mass and body fat percentage were revealed in men. Among women, considerably weaker correlations of BMD with body composition and physical activity were noted than in men. BMD in the distal part correlated only with lean body mass, soft lean mass and body fat percentage. The strongest relationship between physical activity and bone mineral status parameters was noted for BMD in men. In women, physical activity did not affect BMD. CONCLUSIONS: Physical activity has the most significant effect on bone status especially in men.